A New Pandemic Coronavirus COVID-19 Evolutionary Relation, Transmission, Infectivity and Immunity - Salman, Afrah (Al-Nahrain Journal of Science, 2021)
The currently COVID-19 virus appeared in China in the beginning at December 2019, infected more than thousands of humans, by causing a severe respiratory disease (like pneumonia), in severe cases lead to death. Rapidly spread all over the world and cause a pandemic as announced by the world health organization (WHO), this virus showed a close evolutionary relation to other type of coronavirus, the sever acute respiratory syndrome coronavirus SARS-CoV, which is responsible for the endemic that appeared in 2002-2003. In this review it was been focused on the causes of the pandemic as well as study the results of the latest research in connection with the previous publications and the role of molecular genetic analysis study of the viral RNA to get more knowledge about the evolutionary relation, infectivity and immunity.